Future perspectives of thermal energy storage with metal hydrides - Manickam, K.; Mistry, P.; Walker, G.; Grant, D.; Buckley, Craig; Humphries, Terry; Paskevicius, Mark; Jensen, T.; Albert, R.; Peinecke, K.; Felderhoff, M. (Elsevier Ltd, 2019)
Thermochemical energy storage materials have advantage of much higher energy densities compared to latent or sensible heat storage materials. Metal hydrides show good reversibility and cycling stability combined with high enthalpies. They can be used for short and long-term heat storage applications and can increase the overall flexibility and efficiency of solar thermal energy production. Metal hydrides with working temperatures less than 500 °C were in the focus of research and development over the last years. For the new generation of solar thermal energy plants new hydrides materials with working temperatures above 600 °C must be developed and characterized. In addition to thorough research on new metal hydrides, the construction and engineering of heat storage systems at these high temperatures are challenging. Corrosion problems, hydrogen embrittlement and selection of heat transfer fluids are significant topics for future research activities.